Pengaruh Faktor Motivasi, Komitmen Organisasi dan Kepemimpinan Terhadap Kinerja Dosen dengan pendekatan Eksplanatori pada STMIK Kharisma Makassar - Fitriana M Sabir (STMIK KHARISMA Makassar, 2016)
The inadequate performance of the lecturers in carrying out their duties may be exacerbated by low motivation of the principal duties, also including factors organizational commitment and leadership role therein. And supported by the results of previous research are varied and not always in line with the theory of the background in this study. The study aims to look at how much influence Motivation, Organizational Commitment and Leadership on the performance faculty at Kharisma STMIK Makassar. This study uses primary data collection techniques namely data collection techniques using questionnaires, interviews and direct observation with a total sample of 43 by using a multiple linear regression analysis tools. The results showed that partially, motivation positive and significant impact on Lecturer Performance, Organizational Commitment positive and significant impact on the Performance Lecturer and Leadership does not significantly influence Lecturer performance. Also Motivation, Organizational Commitment and Leadership effect together or simultaneously to the lecturer performance. It is recommended that the university leaders should provide motivation to the lecturers in order to become a better faculty performance and optimal. Conversely, a lecturer violating the institution should be given panisme accordance with the level of the offense. Lecturers who are committed and loyal to the institution certainly has a high motivation to be a better lecturer and achievement.